Effect of the compound GIZH -290 and levetiracetam on epileptic activity in rat brain structures on EEG models of bemegrid-induced seizures - T. A. Voronina; S. A. Litvinova; I. G. Kovalev (LLC "Publisher OKI", 2021)
The effect of levetiracetam (a derivative of 4-phenylpyrrolidone) and its original analog, the compound GIZH-290, on primary generalized epileptic activity (EpA) in rat brain structures (sensorimotor cortex, dorsal hippocampus-CA3 field and lateral hypothalamus field) on EEG models of bemegridinduced seizures was studied. It was found that EpA, after the introduction of bemegrid, appears in 1-2 minutes in the form of prolonged generalized high-amplitude discharges and is registered within 3 hours. GIZH-290 (5 mg/kg, intraperitoneal, 15 minutes after bemegrid) causes a significant (p < 0.05) decrease in the number of epileptic discharges in the cortex and at the level of the trend in the hippocampus, which is accompanied by a decrease in the amplitude of the Epi-discharges. Levetiracetam at a dose of 200 mg / kg does not significantly change the severity of paroxysmal activity (the number of convulsive discharges and their duration) caused by bemegrid.